The Effect Of Work Conflict On Employee Performance At The West Binjai District Office - M. Safwan Siddin; Mesra B (International Journal of Management, Economic and Accounting, 2024)
This study aims to analyze the influence of work conflict on employee performance at the West Binjai District Office. Work conflicts are often a factor that affects employee performance, both positively and negatively, depending on how they are managed. In this study, work conflicts are measured by four types of conflicts and employee performance is measured through indicators of work product quantity, quality of work products, efficiency, initiative, thoroughness, leadership, honesty, and creativity. The type of research used is quantitative associative casual with a simple linear regression approach. The population in this study is 80 employees in the West Binjai District Office, with a saturated sample that includes all employees. Data was collected through a questionnaire distributed to respondents, and data analysis was carried out using SPSS version 25.0. The results of the regression test showed that Work Conflicts had a negative and significant effect on Employee Performance at the Binjai City Regional Secretariat Office. This can be seen from the t-count value of 2.147, which is greater than the t-table of 1.99085, and the significance value of 0.000 which is smaller than 0.05. A regression coefficient of 39.194 means that if there is no Labor Conflict, then there has been Employee Performance of 39.194 points. This coefficient indicates that every 1 point increase in Labor Conflict will lead to a decrease of 0.030 points in Employee Performance. This negative value indicates an inverse relationship between Work Conflict and Employee Performance. Therefore, it is important for the management of the West Binjai District Office to manage work conflicts well in order to improve employee performance and the quality of public services provided.